Potent Anti-Inflammatory Activity of Ursolic Acid, a Triterpenoid Antioxidant, Is Mediated through Suppression of NF-κB, AP-1 and NF-AT - Checker R. (Public Library of Science (PLoS), 2018)
10.1371/journal.pone.0031318